2010
DOI: 10.1007/s00251-010-0486-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic plasticity of the MHC class I A region in rhesus macaques: extensive haplotype diversity at the population level as revealed by microsatellites

Abstract: The Mamu-A genes of the rhesus macaque show different degrees of polymorphism, transcription level variation, and differential haplotype distribution. Per haplotype, usually one “major” transcribed gene is present, A1 (A7), in various combinations with “minor” genes, A2 to A6. In silico analysis of the physical map of a heterozygous animal revealed the presence of similar Mamu-A regions consisting of four duplication units, but with dissimilar positions of the A1 genes on both haplotypes, and in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 66 publications
1
59
0
Order By: Relevance
“…Selection pressure by pathogens drives the generation of polymorphism in the functional genes (Parham et al 1995). The details of these processes and the outcomes vary greatly between species: humans, for example, have a fixed complement of three classical MHC class I genes (HLA-A, HLA-B and HLA-C); rhesus macaques in contrast have very variable combinations of duplicated Mamu-A and Mamu-B genes, thus demonstrating region configuration polymorphism (Bodmer 1987;Bonhomme et al 2008;Doxiadis et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Selection pressure by pathogens drives the generation of polymorphism in the functional genes (Parham et al 1995). The details of these processes and the outcomes vary greatly between species: humans, for example, have a fixed complement of three classical MHC class I genes (HLA-A, HLA-B and HLA-C); rhesus macaques in contrast have very variable combinations of duplicated Mamu-A and Mamu-B genes, thus demonstrating region configuration polymorphism (Bodmer 1987;Bonhomme et al 2008;Doxiadis et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…However, this in itself is not always straightforward due to the fluid, and sometimes rapidly evolving nature of the MHC region. In the case of the rhesus macaque for example, there are variable numbers of 'A' locus genes, due to block duplications and recombination (Doxiadis et al 2011). These have been named A1 to A7 based to an extent on phylogenetic relationships; however, it has been shown that their relative map positions can vary substantially between haplotypes.…”
mentioning
confidence: 97%
“…This can be seen at the level of genetic polymorphism, but also in variations in gene number and haplotype complexity (Kelley et al 2005;Doxiadis et al 2011). Livestock species are crucial to global food security; thus, it is important to gain a detailed understanding of these genes and their role in disease resistance in such species.…”
mentioning
confidence: 99%
“…In humans, the classical HLA-A, -B, and -C genes are restricted to a single locus, and are characterized by extensive polymorphism [14]. In the rhesus macaque, the homologs of HLA-A and -B, designated Mamu-A and -B respectively, are present, while the ortholog of HLA-C is absent [15].Contrary to HLA, the Mamu-A and -B genes show a lesser degree of polymorphism but are expanded in their copy number, leading to many haplotypes with variable gene content, referred to as region configurations [16,17]. In both species, the MHC has evolved in its own manner; functionally, however, these molecules behave in the same way.…”
mentioning
confidence: 99%
“…Contrary to HLA, the Mamu-A and -B genes show a lesser degree of polymorphism but are expanded in their copy number, leading to many haplotypes with variable gene content, referred to as region configurations [16,17]. In both species, the MHC has evolved in its own manner; functionally, however, these molecules behave in the same way.…”
mentioning
confidence: 99%